POTENSI BISNIS PERBANKAN SYARIAH INDONESIA TAHUN 2024: PELUANG DAN TANTANGAN - Ickhsanto Wahyudi; Ibnu Qizam; Erika Amelia; Indo Yama (JURNAL LENTERA BISNIS, 2024)
This study analyzes the growth outlook, opportunities, and challenges for Islamic banking in Indonesia approaching the 2024 vision to become the global Islamic economic hub. Despite positive historical trends, research comprehensively examining medium-term projections across key metrics and strategic policy implications is limited. This paper addresses the gap through qualitative interviews with experts to forecast growth in assets, financing, and customers by 2024. High potentials in untapped markets are weighed against challenges in accelerating digital transformation and reforms needed in regulation, technology, and human resources. Key recommendations will be presented for regulators and industry players to optimize growth momentum amidst Indonesia’s Islamic economy goals. The results are expected to enrich academic literature and provide regulators and practitioners strategic inputs to strengthen policies, infrastructure, capabilities, and market access. Further quantitative research can build upon these findings for deeper projections and insights forward. Keywords: Islamic banking, Islamic finance, prospects, challenges, policy, Indonesia